Surfboard Related Orbital and Periocular Injury. Issue 6 (29th September 2022) - Davidov, Bar; Leibovitch, Igal; Mezad-Koursh, Daphna; Feldman, Ilan; Cnaan, Ran Ben
Abstract : Purpose: The objective of this study is to present the complexity of surfboard related orbital and periocular injuries and to discuss the different prevention aspects of such injuries. Methods: A retrospective review was performed on surfing related orbital and periocular injuries cases in a single tertiary medical center over a period of 10 years. Results: Six patients at a mean age of 34 (range 20–50) years were evaluated. All were amateur surfers. Five patients had an orbital fracture, 3 had a full thickness eyelid laceration, 3 had lacrimal drainage system damage and 3 had intraocular findings related to trauma, but no perforation of the globe was observed. Two patients had complete optic nerve avulsion or transection, 1 of them had extraocular muscle transection. Five patients underwent surgery and 2 required an additional surgical intervention. At the end of follow-up, 3 patients had an unrepairable lacrimal drainage damage, 2 had a malposition of an eyelid, 2 eyes remained blind, 1 patient had a hypoglobus, and 1 had hypoesthesia in distribution of infraorbital nerve. Conclusions: Surfboard related orbital injuries may cause a severe orbital injury, which may debilitate and disable a previously active and healthy group of young people. Hence, protective gear wear should be more vigorously encouraged as already been done in other sports.